2017
DOI: 10.1016/j.yexcr.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characterization of endometrial mesenchymal stem-like cells activity during the menstrual cycle

Abstract: The human endometrium is a highly dynamic tissue with the ability to cyclically regenerate during the reproductive life. Endometrial mesenchymal stem-like cells (eMSCs) located throughout the endometrium have shown to functionally contribute to endometrial regeneration. In this study we examine whether the menstrual cycle stage and the location in the endometrial bilayer (superficial and deep portions of the endometrium) has an effect on stem cell activities of eMSCs (CD140bCD146 cells). Here we show the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Intriguingly, the SP4 cells had the highest proliferation capacity and were enriched in the menstrual phase samples (chi-squared test, p < 0.0001). We have demonstrated that eMSCs from the menstrual phase have a higher proliferation ability than those from the secretory phase [8], and may be attributed to the enrichment of the SP4 cells in the menstrual phase. In addition, SP1 and SP4 showed a transdifferentiation potential to the epithelial cell lineage (Figure S4B).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Intriguingly, the SP4 cells had the highest proliferation capacity and were enriched in the menstrual phase samples (chi-squared test, p < 0.0001). We have demonstrated that eMSCs from the menstrual phase have a higher proliferation ability than those from the secretory phase [8], and may be attributed to the enrichment of the SP4 cells in the menstrual phase. In addition, SP1 and SP4 showed a transdifferentiation potential to the epithelial cell lineage (Figure S4B).…”
Section: Discussionmentioning
confidence: 89%
“…Endometrial aspirates from the menstrual phase of three women and four full-thickness endometrium from the secretory phase of four women were used in this study (Table S1). After enzyme dispersion of the tissues, the CD140b + CD146 + cells were obtained from endometrial stromal cells by serial magnetic microbeading [8,10]. They were subjected to scRNA-seq on a 10X genomics platform.…”
Section: Overview Of Single-cell Transcriptomic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The isolation procedure of endometrial cells was carried out as described [5]. The tissues were minced and digested with PBS containing collagenase type III (0.3 mg/ml, Worthington Biochemical Corporation, NJ, USA) and deoxyribonuclease type I (40 μg/ml, Worthington Biochemical Corporation) for one hour at 37 o C. Red blood cells were removed using Ficoll-Paque (GE Healthcare, Uppsala, Sweden) densitygradient centrifugation.…”
Section: Single Cell Suspensions Of Endometrial Epithelial and Stromamentioning
confidence: 99%